A comparative study on Entropy-TOPSIS and MEREC-TOPSIS methods to solve the class representative selection problem / Nurul Ain Nazirah Ahmad Khaidir, Nurul Farahana Adnan and Danial Ahmad - Ahmad Khaidir, Nurul Ain Nazirah; Adnan, Nurul Farahana; Ahmad, Danial (2023)
This study is about selecting the best class representative in a public university. In this study, it is focused on the application of Entropy-Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) and Method Based of the Removal Effects of Criteria (MEREC)-TOPSIS in solving class representative selection problem. This study discusses the problem that a class of a public university commonly has, which is choosing the best candidate for their class representative. The objectives of this study are to integrate the Entropy method and MEREC with TOPSIS methods in solving the class representative selection problem, to select the best class representative by using the Entropy-TOPSIS method and MEREC-TOPSIS method and to compare the outcome between Entropy-TOPSIS method and MEREC-TOPSIS method in solving the class representative selection problem.